Subclinical Bulimia Predicts Conduct Disorder in Middle Adolescent Girls. (16th April 2012) - Viinamäki, Anni; Marttunen, Mauri; Fröjd, Sari; Ruuska, Jaana; Kaltiala‐Heino, Riittakerttu
Abstract: This study investigates the comorbidity and longitudinal associations between self‐reported conduct disorder and subclinical bulimia in a community‐based sample of Finnish adolescents in a 2‐year prospective follow‐up study. There are 2070 adolescents who participated in the survey as ninth graders (mean age 15.5) and followed‐up 2 years later. The Youth Self‐Report Externalizing scale was used to measure conduct disorder and DSM‐IV‐based questionnaire to measure bulimia. Co‐occurrence of female conduct disorder and subclinical bulimia was found at ages 15 and 17. Subclinical bulimia among girls at age 15 was a risk factor for conduct disorder at age 17, but conduct disorder at age 15 was not predictive of subclinical bulimia at age 17. The pathway from bulimia to conduct disorder may be suggestive of an association with future borderline personality disorder among girls. Copyright © 2012 John Wiley & Sons, Ltd and Eating Disorders Association.